2017
DOI: 10.1016/j.appet.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Deal or no deal? The prevalence and nutritional quality of price promotions among U.S. food and beverage purchases

Abstract: Objective This study examines trends in the prevalence of price promotions among packaged food and beverage purchases, differences in prevalence by household race/ethnicity or income, and the association between price promotions and the nutritional profile of purchases. Design This cross-sectional study utilizes a dataset of 90 million purchases from 38,744 (2008) to 45,042 (2012) US households in 2008–2012. Chi-square tests were used to examine whether the proportion of purchases with price promotions chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 50 publications
1
20
3
Order By: Relevance
“…The health implications of beverage price promotions depend on their influence on healthy and unhealthy beverage choices – a function of both the frequency and magnitude of price promotions on healthy and unhealthy beverages and consumer responses to such price promotions. While studies from the UK and US show that the impact of price promotions on purchasing behaviour is similar for healthy and less healthy foods, 18,19 comparable analyses are not available in the Australian context. Finally, it is important to acknowledge that ‘everyday low prices’ were not included as a price promotion in our study as we were interested in temporary (not ‘everyday’) price reductions.…”
Section: Discussionmentioning
confidence: 99%
“…The health implications of beverage price promotions depend on their influence on healthy and unhealthy beverage choices – a function of both the frequency and magnitude of price promotions on healthy and unhealthy beverages and consumer responses to such price promotions. While studies from the UK and US show that the impact of price promotions on purchasing behaviour is similar for healthy and less healthy foods, 18,19 comparable analyses are not available in the Australian context. Finally, it is important to acknowledge that ‘everyday low prices’ were not included as a price promotion in our study as we were interested in temporary (not ‘everyday’) price reductions.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-four studies were included in this scoping review [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Information on customer purchasing assessment methodologies used across studies is shown in ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies (44.1%) examined purchasing outcomes across racial and/or ethnic groups [ 27 , 29 , 30 , 39 , 42 , 43 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 53 , 54 ]. All studies examined purchasing among NHW, 14 examined purchasing among NHB, 14 studied purchasing among Hispanic, nine examined purchasing among non-Hispanic Other (or a different author definition that collapsed multiple racial/ethnic groups), and three investigated purchasing among Asian (using the author definition).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations